THE SPECIFICITY OF PREVAILING VALUE-MEANING ORIENTATIONS IN COLLEGE TECHNICAL SPECIALTIES STUDENT’S - Вербова, Юлія Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article is aimed to reveal the problem of technical specialties colleges student’s value-meaning orientations. The main theoretical and empirical researches in the sphere of value-meaning self-determination of this category of students are implemented. The specificity of respondent’s general meaning of life and its components, predominant values are analyzed. The correlation between the meaning of life and value orienta-tions structuring of technical specialties colleges student is conducted.